Study Role of Respiratory Syncytial Virus Associated with Infection of Respiratory System of Children in AL-Miqdadiya/ Diyala (Institute of Medico-legal Publications Pvt Ltd, 2021)
Human Respiratory Syncytial virus was major cause of viral infection of lower respiratory tract infectionamong infants and young children less 2 years old. HRSV was an enveloped virus with negative sense,single Stranded RNA, belonging to the family of pneumoviridae and genes Orthopneumovirus. This studywas aimed to detection prevalence of respiratory syncytial virus in children with respiratory tract infectionusing Real time - PCR .This study included 50 sample from both gender and ages less than 10 years old,sample were collected from respiratory system patient from 40 patients and 10 controls. Results of currentstudy showed that infection percentage of HRSV was 35% and all controls were un infect. The infectionpercentage of virus was more common in males 47% than females and in children, < one year 37.9% alsohigh frequency were noticed among children who depended on artificial feeding.